A Study Of ‘Learning Style Preferences Among Secondary School Students In Relation To Their Gender And Place Of Living’ (Journal of Namibian Studies : History Politics Culture, 2023)
The study was conducted to analyse preferable learning styles among secondary school students of Visakhapatnam District. The present study is a modest effort to find out the effect of gender and place of Living on learning style preferences of secondary school students. A sample of 300 secondary school students of Visakhapatnam District of Andhra Pradesh was selected for the study. Learning Style Inventory (2012) by Sreekala and Amalraj was used to collect relevant information for the study. Findings of the study indicate that the most preferred learning style among secondary school students is Visual (45.7%) followed by Auditory (21.0%) and Kinaesthetic (15%) It means that most of the secondary school students favoured visual format of learning. It was also found that the most preferred learning style among male and female students was visual learning style. Rural, urban and semi-urban students were found to have no significant difference in their learning styles.